(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The article presents results of a comprehensive study of macro- and micromorphological characters of generative organs of the endangered species Linnaea borealis, which is listed in the Red Data Book of Ukraine. Morphology of pollen grains, flowers and fruits was studied using light and scanning electron microscopy. Additional characters that can be used for solving controversial issues of taxonomy of Caprifoliaceae are revealed. The flower of L. borealis is almost zygomorphic; it has five linear-lanceolate sepals connate at base, tubular, bell-shaped corolla pubescent inside with ribbon-like hairs (only on broadly ovate non-connate parts of petals); two of four stamens are longer than the other two, with filiform filaments and narrow-ellipsoidal, crescent-bent, swinging anthers; carpels with a lower, ovoid ovary, a narrow style, and a funnel-shaped stigma. For the first time we observed a flattened egg-shaped outgrowth on the apical part of the connective of stamens. Palynomorphological peculiarities of L. borealis are specified in detail: pollen grains are 3(4)-colporate, prolate, spheroidal or oblate-spheroidal in shape, in equatorial view elliptical, oval or circular in outline; in polar view slightly 3-lobate, circular-triangular or circular-rectangular; medium- or large-sized, with spinulose exine sculpture. Additional micromorphological characteristics of the fruit surface have been revealed: tuberculate structure and the presence of pubescence with simple and glandular trichomes. Three morphological groups of simple hairs (long, medium, and short ones) and two groups of glandular hairs (short with small heads and long with large heads) are distinguished. Precise localization of hairs of these groups in certain areas of fruits and peduncles is revealed.